Comprehensive Genetic Analysis of Paralogous Terminal Septin Subunits Shs1 and Cdc11 in Saccharomyces cerevisiae. Issue 3 (12th May 2015) - Finnigan, Gregory C; Takagi, Julie; Cho, Christina; Thorner, Jeremy
Abstract: Septins are a family of GTP-binding proteins considered to be cytoskeletal elements because they self-assemble into filaments and other higher-order structures in vivo . In budding yeast, septins establish a diffusion barrier at the bud neck between a mother and daughter cell, promote membrane curvature there, and serve as a scaffold to recruit other proteins to the site of cytokinesis. However, the mechanism by which any septin engages a partner protein has been unclear. The two most related and recently evolved subunits appear to be Cdc11 and Shs1, and the basic building blocks for assembling septin structures are hetero-octameric rods (Cdc11 –Cdc12 –Cdc3 –Cdc10 –Cdc10 –Cdc3 –Cdc12 –Cdc11 and Shs1 –Cdc12 –Cdc3 –Cdc10 –Cdc10 –Cdc3 –Cdc12 –Shs1 ). Loss of Cdc11 is not normally tolerated, whereas cells lacking Shs1 do not appear grossly abnormal. We established several different sensitized genetic backgrounds wherein Shs1 is indispensable, which allowed us to carry out the first comprehensive and detailed genetic analysis of Shs1 in vivo . Our analysis revealed several novel insights, including: (i) the sole portion of Shs1 essential for its function is a predicted coiled-coil-forming segment in its C-terminal extension (CTE); (ii) the CTE of Cdc11 shares this function; (iii) this role for the CTEs of Cdc11 and Shs1 is quite distinct from that of the CTEs of Cdc3 and Cdc12 ; and (iv) heterotypic Cdc11 and Shs1 junctions likely occur in vivo . Related article in GENETICS : Finnigan, G. C. et al., 2015 The Carboxy-Terminal Tails of Septins Cdc11 and Shs1 Recruit Myosin-II Binding Factor Bni5 to the Bud Neck in Saccharomyces cerevisiae . Genetics 200: 843 –862 .